Evolution of Microstructure, Properties and Texture of a Two‐Phase Low‐Carbon Steel at Cold Asymmetric Rolling. Issue 8 (12th January 2017) - Grydin, Olexandr; Andreiev, Anatolii; Briukhanov, Arkadii; Briukhanova, Zoia; Schaper, Mirko
Abstract : Asymmetric rolling allows shear strains in a material to be pre‐determined, along with a corresponding texture, resulting in a refinement of the microstructure and enhancement of the mechanical properties. However, the effect of asymmetric rolling, with high values of asymmetric factor on metals with a multi‐phase microstructure has not been thoroughly investigated yet. Thus, experiments are conducted involving asymmetric cold rolling of ferrite‐pearlite low‐carbon steel with the 1:4 ratio of rolls speeds, as well as a comparison to conventional symmetric rolling. The microstructure, as well as the texture of asymmetrically rolled strips are, then, analyzed and compared with symmetrically rolled specimens. This analysis shows significant grain refinement in both symmetrically and asymmetrically rolled strips due to the formation of developed cellular dislocation substructures. Analysis of texture in strips after two passes of asymmetric and symmetric rolling show the presence of isotropic texture component {111}<112>, which leads to the so‐called "texture strengthening". Furthermore, in asymmetric rolled strip an axial texture {110} with axis coinciding with normal direction is also observed, that is, an important component of shear texture. Abstract : Asymmetric cold rolling instead of conventional symmetric cold rolling of low‐carbon steels promises significant reduction of rolling forces and grain refinement with simultaneous improvement of mechanical properties and drawability. Rolling forces at asymmetric cold rolling of steel 22MnB5 could be up to 50% lower than at conventional symmetric cold rolling.